Effects of Size Reduction on the Electrical Transport Properties of 3D Bi Nanowire Networks. (27th January 2021) - Wagner, Michael Florian Peter; Paulus, Anna Sarina; Brötz, Joachim; Sigle, Wilfried; Trautmann, Christina; Voss, Kay‐Obbe; Völklein, Friedemann; Toimil‐Molares, Maria Eugenia
Abstract: 3D nanowire networks are fascinating systems for future microelectronic devices. They can be handled like macroscopic objects, while exhibiting properties of nanoscale materials. Here, the fabrication of free‐standing 3D bismuth nanowire networks with well‐controlled and systematically adjusted wire diameter and interconnectivity is presented. The samples are fabricated by pulse electroplating of bismuth into the pores of ion track‐etched membranes using an aqueous electrolyte. By optimizing the growth parameters, homogeneously grown, mechanically self‐supporting and free‐standing networks without a supporting matrix are achieved. Cross‐plane Seebeck coefficient and electrical resistance values are investigated as a function of nanowire diameter and temperature. The unique characteristics of these highly interconnected and mechanically self‐supported Bi 3D nanowire networks offer exciting perspectives for their implementation in, e.g., infrared detection based on thermoelectric effects, sensing, and THz applications. Abstract : Free‐standing 3D bismuth nanowire networks are fabricated by pulse electrodeposition in etched ion‐track membranes. Cross‐plane Seebeck coefficients and electrical resistance are measured as a function of temperature. The unique characteristics of these highly interconnected and mechanically self‐supported Bi 3D nanowire networks offer exciting perspectives for their implementation in e.g. thermoelectric and sensing applications.